Δ1-Dehydrogenation and C20 Reduction of Cortisone and Hydrocortisone Catalyzed by Rhodococcus Strains - Costa, Stefania (Molecules, 2020)
Prednisone and prednisolone are steroids widely used as anti-inflammatory drugs. Development of the pharmaceutical industry is currently aimed at introducing biotechnological processes and replacing multiple-stage chemical syntheses. In this work we evaluated the ability of bacteria belonging to the Rhodococcus genus to biotransform substrates, such as cortisone and hydrocortisone, to obtain prednisone and prednisolone, respectively. These products are of great interest from a pharmaceutical point of view as they have higher anti-inflammatory activity than the starting substrates. After an initial lab-scale screening of 13 Rhodococcus strains, to select the highest producers of prednisone and prednisolone, we reported the 200 ml-batch scale-up to test the process efficiency and productivity of the most promising Rhodococcus strains. R. ruber, R. globerulus and R. coprophilus gave the Δ1-dehydrogenation products of cortisone and hydrocortisone (prednisone and prednisolone) in variable amounts. In these biotransformations, the formation of products with the reduced carbonyl group in position C(20) of the lateral chain of the steroid nucleus was also observed (i.e., 20β-hydroxy-prednisone and 20β-hydroxy-prednisolone). The yields, the absence of collateral products, and in some cases the absence of starting products allow us to say that cortisone and hydrocortisone are partly degraded.